Training Needs for Kindergarten Teachers in The Light of Economic Practices (Journal of Hama University, 2021)
The current research aims to identify the training needs of kindergarten teachers in light of economic practices, and the researcher used the descriptive approach, where the research was applied to a sample of kindergarten teachers, numbering (95) teachers, and the sample was chosen in a cluster random manner, and to achieve the research objectives a list of appropriate economic practices for kindergarten children was used, in addition to a questionnaire of the training needs of teachers, and the results indicated the existence of a number of training needs for kindergarten teachers in light of economic practices: (working in a team, selling, buying, marketing, promotion), the degree of need was very great, and the most urgent of them are represented in the following order:First place: after working in a team, and the most needed was "the application of the four stages of team building."Second place: after promotion, and the most needed one was "Applying advertising design steps to promote the product."Third place: after the purchase, and the most needy was "Know the skills of negotiating with the seller when buying."Fourth place: After the sale, and the most needy "Use appropriate strategies to train children to sell."Fifth place: after the promotion, and the most needy "know the appropriate marketing strategies for the product." In light of the results, the researcher suggested setting up training courses for kindergarten teachers to train them on how to employ economic practices and use them in different educational situations, in kindergarten, and pay attention to integrating economic practices into the kindergarten curriculum.